Implementasi Kebijakan Ketertiban Umum Dan Ketentraman Masyarakat Pada Gelandangan Dan Pengemis Di Kota Tangerang Selatan - Aldira Lindawati; Abdul Rahman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
There are many problems that have become social phenomena in several regions in Indonesia related to PPKS, problems regarding PPKS in the form of vagrants and beggars also occur in South Tangerang City. The purpose of this research is to find out and analyze how the implementation of the South Tangerang City Regional Regulation in the Government of Social Welfare Services in South Tangerang City. This type of research uses qualitative methods with descriptive research types. Data collection techniques using observation, interviews, and documentation. . The data analysis technique used is using the tringulation technique. The results of the study concluded that Policy Implementation still experiences obstacles, especially in the benefits generated, the Degree of Change, and Program Implementation. Lack of socialization and lack of handling of vagrants and beggars are obstacles in this implementation.